Simulating urban growth driven by transportation networks: A case study of the Istanbul third bridge - Ayazli, Ismail Ercument; Kilic, Fatmagul; Lauf, Steffen; Demir, Hulya; Kleinschmit, Birgit (ELSEVIER SCI LTD, 2015)
Increasing populations and the related transport volumes are problematic for metropolitan regions in Istanbul especially due to the separation of the city by the Bosphorus strait, which creates significant congestion, delays, and carbon dioxide emissions. A third bridge north of the two existing bridges that will bypass the urban areas in Istanbul is under construction to address these challenges. The new Yavuz Sultan Selim Bridge project will transect the most important natural areas. The main purpose of this paper is to investigate urban growth driven by transport networks as observed after the construction of the two existing bridges and the probable impact the third bridge will have on land use and land cover (LULC) via a cellular automata (CA) based simulation technique. The time periods selected for model calibration were 1972, 1987, 2002, and 2009 because the first bridge (Bosphorus Bridge) was built in 1973 and the second bridge (Fatih Sultan Mehmet Bridge) in 1988. An urban growth simulation model was generated for the year 2030, and a change detection analysis was performed between 1972-2009 and 2009-2030 to determine the probable natural areas threatened by urbanization. According to the results, Istanbul will continue to grow northward with 41% of forested areas and 28% of fragile ecosystem areas transforming into urban areas between 2009 and 2030. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Urban growth; Cellular automata; LULC change; Istanbul; Third bridge; Transportation network; CELLULAR-AUTOMATON MODEL; SAN-FRANCISCO; URBANIZATION; SCENARIOS; DYNAMICS; PATTERNS; REGION; HEALTH; SPRAWL; LINKS; Environmental Sciences & Ecology